Diagnostic value of videotoracoscopy in the conditions of antituberculosis institution - Prosvyetov, Yu. V.; Gusarova, А. Yu.; Evsa, V. A. (Modern medical technology, 2021)
The article presents the results of diagnostic videothoracoscopy during three years that were performed in an anti-tuberculosis institution. Patients were radiographically discovered to have chest pathology. No bacteria discharge was detected. To verify the diagnosis, 136 patients underwent videothoracoscopy with biopsy. Evaluation of the obtained biopsy results showed that, only 48 patients (35,3%) had specific tuberculous lesions verified. In other cases, a different pathology was noted: sarcoidosis, oncopathology, nonspecific inflammation, and idiopathic pulmonary fibrosis. Thus, the results of this study confirmed the high efficiency of the videothoracoscopy method for verifying the diagnosis in patients without bacterial discharge.